2013
DOI: 10.1007/s12032-013-0457-3
|View full text |Cite
|
Sign up to set email alerts
|

Sequential docetaxel as adjuvant chemotherapy for node-positive or/and T3 or T4 breast cancer: clinical outcome (Mansoura University)

Abstract: This trial compared 6 cycles of fluorouracil, epirubicin, and cyclophosphamide (FEC) with a sequential regimen of 3 cycles of FEC followed by 3 cycles of docetaxel (FEC-D) as adjuvant treatment for women with node-positive or/and T3 or T4 breast cancer. Between January 2006 and January 2010, 657 patients with operable breast cancer were randomly assigned to either FEC every 21 days for 6 cycles, or 3 cycles of FEC followed by 3 cycles of docetaxel, both given every 21 days. Radiotherapy was mandatory for all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Significant relative risk reductions were observed in the hormone positive, HER2-positive, and Ki67 ≥20% (Coudert et al, 2012). This is consistent with an Egyptian study done by (Sakr et al, 2013) using the same regimen as the French trial. Five-year DFS rates were 74 % with FEC and 78 % with FEC-D (p=0.013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Significant relative risk reductions were observed in the hormone positive, HER2-positive, and Ki67 ≥20% (Coudert et al, 2012). This is consistent with an Egyptian study done by (Sakr et al, 2013) using the same regimen as the French trial. Five-year DFS rates were 74 % with FEC and 78 % with FEC-D (p=0.013).…”
Section: Discussionsupporting
confidence: 87%
“…An Australian study found that the Egyptian women had the highest breast cancer rates of all Middle Eastern immigrants to Australia (McCredie, 1994). Egyptian publications conducted in Egypt in the adjuvant breast cancer setting are scarce (Abd-El-Moneim et al, 2011;Hamza et al, 2011;Sakr et al, 2013) Over three decades Montemurro and (Montemurro and Aglietta, 2009). The feasibility of six cycles of either docetaxel plus cyclophosphamide (TC6) or sequential taxane and anthracycline regimen (T-FEC) in Japanese patients with HER2-negative early breast cancer, was assessed (Abe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Of 4324 potentially relevant articles, 31 articles (24 trials) were included in this study. 7,8,1422,3049 The results of the quality assessment of the trials according to the Cochrane risk-of-bias tool are shown in eTable 1 in the Supplement. Twenty-one trials included only women and in 3 trials there was not a clear description of criteria about sex.…”
Section: Resultsmentioning
confidence: 99%
“…In the 1990s, taxanes were introduced in clinical practice, leading to more complex drug sequences and combinations. Indeed, the therapeutic arsenal could be enriched by regimens such as AC→T, TAC, FEC→D, and TC, which improved survival against previous standards . A parallel branch of research focused on neo‐adjuvant setting.…”
Section: Introductionmentioning
confidence: 99%